The State of Corporate Governance : Experience from Country Assessments - Frémond, Olivier (The World Bank, 2002)
Corporate governance deals with the ways in which the rights of outside suppliers of equity finance to corporations are protected and receive a fair return. Good practices reduce the risk of expropriation of outsiders by insiders and thus the cost of capital for issuers. Capaul and Fremond review the experience of the preparation of 15 corporate governance country assessments across five continents. The assessments have been prepared under the umbrella of the joint World Bank/IMF initiative of the "Reports on the Observance of Standards and Codes" (ROSCs). The assessments focus on the rights of shareholders, the equitable treatment of shareholders, the role of stakeholders, disclosure and transparency, and the duties of the board of listed companies, and use the OECD Principles of Corporate Governance as benchmark. The authors give an overview of the actual and potential contribution of the assessments to policy dialogue, diagnostic and strategic work, lending and nonlending operations, and technical assistance and capacity, and presents the unfinished agenda. This paper—a product of the Corporate Governance Unit, Private Sector Advisory Services Department—is part of a larger effort in the department to disseminate lessons learned in the assessment of the compliance of countries to global standards. The authors may be contacted at ofremond@worldbank.org or mcapaul@worldbank.org